The Fund Agreement in the Court, Vol. IV - Gold, Joseph (International Monetary Fund, 1989)
Written by Joseph Gold, former General Counsel and now Senior Consultant at the IMF, these volumes contain discussions of the ever-increasing body of cases in which the Articles have had bearing on issues before the courts.